2022
DOI: 10.1111/ele.13938
|View full text |Cite
|
Sign up to set email alerts
|

Sex roles in birds: Phylogenetic analyses of the influence of climate, life histories and social environment

Abstract: Sex roles describe sex differences in courtship, mate competition, social pair-bonds and parental care. A key challenge is to identify associations among the components and the drivers of sex roles. Here, we investigate sex roles using data from over 1800 bird species. We found extensive variation and lability in proxies of sex roles, indicating remarkably independent evolution among sex role components.Climate and life history showed weak associations with sex roles. However, adult sex ratio is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 69 publications
(107 reference statements)
0
40
3
Order By: Relevance
“…Thus, positive values represent male-biased ornamentation, zero represents unbiased ornamentation, and negative values represent female-biased ornamentation. The average score of five body regions correlated well with three independent datasets of dichromatism: Spearman rank correlations, rs = 0.705, N = 5825 species, p < 0.001 42 , rs = 0.867, N = 905 species, p < 0.001 87 , and rs = 0.542, N = 855 species, p < 0.001 86,88 .…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, positive values represent male-biased ornamentation, zero represents unbiased ornamentation, and negative values represent female-biased ornamentation. The average score of five body regions correlated well with three independent datasets of dichromatism: Spearman rank correlations, rs = 0.705, N = 5825 species, p < 0.001 42 , rs = 0.867, N = 905 species, p < 0.001 87 , and rs = 0.542, N = 855 species, p < 0.001 86,88 .…”
Section: Methodsmentioning
confidence: 73%
“…In practice, sexual size dimorphism was calculated for three traits representing body size (body mass (g), tarsus length (mm) and wing length (mm)) and was calculated as log (male trait value/female trait value) 85 . Sexual dichromatism was obtained following Gonzalez-Voyer et al ( 2022) 86 . In short, the mean value of plumage dimorphism is estimated from five body regions (head, back, belly, wings and tail).…”
Section: Explanatory Variables In Statistical Modelsmentioning
confidence: 99%
“…The absence of a relationship may be due to the fact that most passerines have a monogamous mating system (Lack 1968), and therefore polygyny frequency may not be an ideal proxy to measure mating opportunities. In addition, a study with a much broader sample of species found rather weak correlations between different sex role components (that is estimates of intra-sexual competition (sex size dimorphism), mate attraction (sexual dichromatism), mating system and parental care), including a weak correlation between mating system and the investment in parental care by both sexes (Gonzalez-Voyer et al 2022). Such weak correlations between sex role components could explain why we did not find an association between the mating system and the presence of carotenoid-dependent plumage coloration.…”
Section: Discussionmentioning
confidence: 99%
“…Liker et al (2015) compiled detailed information on relative investment by each sex in six components of avian parental care from reference books, and published literature (references in Liker et al 2015 updated in Gonzalez-Voyer et al 2022). We focus here on only three components: nest building, incubation, and chick feeding, which are the ones for which information was available for the greatest number of species.…”
Section: Methodsmentioning
confidence: 99%
“…Substantial emphasis has been placed on conventional “sex roles” for female and male animals, in line with the Darwin-Bateman paradigm of sexual selection ( Janicke et al, 2016 ; Gonzalez-Voyer et al, 2022 ). This binary framing reinforces what is expected for sex-specific courtship, competition, parental care, and their endocrinological correlates, thereby limiting how we examine and interpret variation in natural history ( Ah-King and Ahnesjö, 2013 ).…”
Section: Barriers To Our Understanding Of Avian Endocrinology In Femalesmentioning
confidence: 99%